Imam Al-Ṭabarī’s Analysis of the Polemic Position of Basmala in Surah Al-Fatihah: A Study of Paradoxical Views - Muin, Abd; Aswadi, Aswadi; Zakka, Umar; Tohir, M. (Jurnal Ushuluddin, 2025)
The diversity of interpretations of the Holy Qur’an is inevitable, largely due to methodological differences, specifically the riwāyah method and ijtihad. In the debate over whether the recitation of the basmalah is part of al-Fatihah, some commentators consistently employ the riwāyah method. However, al-Ṭabārī approached the status of the basmalah recitation in al-Fatihah solely through ijtihad. Consequently, the author examines this issue using a qualitative approach grounded in library research. The findings indicate that al-Ṭabārī explicitly opposes the inclusion of the basmalah as part of al-Fatihah. He argues that if the basmalah were indeed a verse of surat al-Fatihah, it would result in the phrase in one Surāh without any separation, and he does not cite any riwāyah sources to support his argument. Al-Ṭabārī's perspective presents a paradox based on two aspects. First, his reliance on pure rationality contradicts the concept of the Holy Qur’an's composition, which is tawqīfī, meaning that al-Ṭabārī should depend on information from the Prophet for legitimization. Second, his rational approach in rejecting the basmalah's status as a verse of al-Fatihah contradicts al-Ṭabārī’s methodological commitment to interpreting the Holy Qur’an based on information from the Prophet and the interpretations of the salaf generation